APLICAÇÃO DO ÍNDICE DE BALNEABILIDADE EM TRÊS BALNEÁRIOS NO MUNICÍPIO DE COXIM/MS - SILVA, Eliene Prado da; GOMES, Ana Carolina Correia de Oliveira; MOREIRA, Suzana Neves; SANTOS, Cleiton Oliveira dos (ANAIS DO ENIC, 2022)
-